The Experience of Holistic Nurse Coaching for Patients With Chronic Conditions. (September 2019) - Delaney, Colleen; Bark, Linda
Purpose: The purpose of this study was to explore and describe the lived experience of adults with chronic conditions receiving holistic nurse coaching.Method: A qualitative phenomenological research design was used for this study. A purposive sample of 15 patients with varied chronic conditions participated. Institutional review board approval was obtained from the participating university prior to data collection. The patients' stories of their experiences with holistic nurse coaching were analyzed using Colaizzi's method of phenomenological analysis.Findings: Eight theme clusters emerged when the formulated meanings were organized into the following categories: (1) Seeking Guidance to Navigate Life's Challenges, (2) Entering a Safe Sacred Place, (3) Feeling Empowered and Accountable, (4) Developing Strategies to Access Different Ways of Knowing, (5) Finding the Answers Within, (6) Making Healthy Behavioral Changes, (7) Forming a New Caring Relationship with Self, and (8) Transforming to a Brand-New Approach to Life.Conclusions: Findings from this study provide insight into experiences of holistic nurse coaching for patients with chronic conditions. Further research is needed to examine the influence of holistic nurse coaching on health outcomes related to chronic conditions such as quality of life, patient empowerment, and targeted metrics related to specific chronic conditions.